Association of date of soing, flowering and wilt incidence in pigeonpea (Cajanus cajan) - CHAUDHARY, R G; KUMAR, KUMUD; NAIMUDDIN, NAIMUDDIN (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during 1995-97 to study the relationship of sowing date and flowering with wiltincidence in pigeonpea. It was found that under agro-climatic conditions of Kanpur vis-a-vis northern plain zone ofIndia, pigeonpea wilt caused by Fusarium udum Butler appeared between 20 September and first fortnight of October in timely sown pigeonpea (Cajanus cajan L. Millsp) depending upon the cessation rains. However, in delayed sowing it may be extended up to first week of November. Date of sowing did influence wilt appearance, its peak period and total wilt incidence, flowering stage of the crop has no association with wilting as reported earlier. It was rather edaphic conditions (temperature and moisture) and resistance level of the pigeonpea genotype that together determined the course of wilt development under sick field conditions. Under Kanpur conditions maximum wilting occurred in October followed by November. These two months offered most optimum soil conditions for pigeonpea wilt.